Komunikasi Agribisnis Dinas Pertanian Dan Perkebunan Dengan Petani Dalam Pengembangan Kopi Robusta Di Kabupaten Kediri - Setiyadi, Heru; Nurul Choirina, Vifi; Nur Atika, Khofifa (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2024)
Regarding the development of robusta coffee, the Kediri Regency Agriculture and Plantation Service (Dispertabun) has been in contact with farmers through Field Extension Officers (PPL). Finding out the model and techniques for agribusiness communication as well as the challenges encountered in implementing Dispertabun's agribusiness communication with farmers to develop robusta coffee in Kediri Regency are the goals to be accomplished. In addition to interactive model data analysis, this study employs a qualitative descriptive methodology (Miles and Huberman). The research findings led to the conclusion that the context of the message being communicated determined the choice of agribusiness communication model. The application of interpersonal (individual) and organizational (group) communication techniques depends on the message's content. It is possible to reduce potential communication obstacles in agriculture. The findings suggest that in order to minimize potential barriers to communication, the Kediri Regency Dispertabun through PPL should continue to maintain appropriate (relevant) communication models and methods. Additionally, keep up the good work in improving agribusiness communication with robusta coffee farmers in order to continue meeting new objectives and targets related to agribusiness communication.